Black carbon measurement in the Artic – is there business potential? Final Report of the Work Package 3 in the Sea Effects Black Carbon Project - Olli-Pekka Brunila; Katariina Ala-Rämi; Tommi Inkinen; Esa Hämäläinen (Turun yliopisto, 2025)
Maritime transport is vital for global business but vulnerable in terms of competitiveness and environmental issues, especially in the Arctic regions. Global warming is proceeding twice as fast in the Polar Regions as in other parts of the world, resulting in a reduction of ice. Therefore, the Arctic sea route is more navigable, allowing an increasing number of ships in the route. Different diesel fuels and BC have a direct impact on climate change and the lowering of arctic ice coverage. In this study, we explore whether measuring black carbon (BC) opens up new business opportunities and designs for an integrated solution.
Fossil fuels are mainly used in sea transport, and emissions such as CO2, SO2, PM, NOx and BC originate mostly from vessel combustion engines. BC is the most important factor in climate change after CO2, and even though its share of international maritime transport is relatively small in terms of total BC emissions (estimations vary between 1 and 2%), the Arctic regions are sensitive to a climate forcer such as BC. If transport continues to increase as estimated, concerns about BC emissions will grow.
The International Maritime Organization (IMO) is the main body responsible for regulating international shipping emissions. The impact of BC in the Arctic regions was first addressed a few years ago by IMO. There is still only limited data available on BC emissions from ships and a limited amount of relative BC mass measurements before and after exhaust treatments. The majority of the previous BC research focused on diesel engines used in road transport.
There are different ways to mitigate BC emissions from ships. The techniques focus on fuel efficiency, slow steaming, exhaust treatments, fuel quality, alternative fuels and different exhaust treatments. The potential of creating business opportunities among these techniques is difficult to estimate before the corresponding regulations are implemented.